Apical-to-Basolateral Transcytosis of Transferrin-Polylysine Conjugates in Caco-2 Cell Monolayers: A Model of Relay Transport of Protein Drug across Epithelial Cells. Issue 1 (2018) - Chen, Yu-Sheng; Zaro, Jennica L; Shen, Wei-Chiang
No abstract available